“I participate. You participate. He participates. We participate. You participate. Do they profit?” Brief reflections on the forms of citizen participation according to the Directive (EU) 2019/944 on the Internal Market of Electricity and the Directive (EU) 2018/2001 on Renewable Energy Sources - Bojarski Pires, Cecília (UNIO – EU Law Journal, 2023)
This article aims to identify the primary forms of citizen participation within the European energy regulatory framework, focusing on decentralised energy production and its intersection with the right to the city and environmental, climate, and energy-related concerns. The article is structured in two sections. The first section addresses the rise of the right to the city, tracing its emergence as a category within urban sociology until its legal recognition as a human right, which guarantees the fruition of urban rights and the promotion of democratic participation in the construction of the urban model. It also analyses the urban phenomenon as a result of the expansion of the urban fabric and a way of life supported by a model of entrepreneurship and commodification of cities. In the second section, there is a brief contextualisation of the development of European energy policy, and it identifies the forms of citizen participation outlined in the Directive (EU) 2019/944 on the Internal Electricity Market, and the Directive (EU) 2018/2001 on Renewable Energy Sources, especially the Citizen Energy Communities (CEC) and Renewable Energy Communities (REC). Finally, the article highlights some risks that should be considered to ensure that market interests do not co-opt mechanisms of citizen participation in the energy sector to the detriment of promoting the right to the city.